The geometrical properties of round Bamboo of Gigantochloa levis and their effects on construction design - Mohd Jamil Abdul Wahab,; Nor Marzuina F.K. Naysir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Round bamboo is reviewed as a highly potential material for building components. However, the assessable data of the geometrical variability of Malaysian bamboos proposed as structural members are greatly lacking. A study was conducted to establish the geometric properties of Gigantochloa levis culms and to derive the important parameters that will affect engineering design. The evaluations were based on the internode length, culm diameter, wall thickness, and the second moment of area with respect to the height of the culm. Most internode sections measured between 35 and 50 cm. An internodal crack could severely change the cross-sectional geometry of the culm. Two major factors concerning culm diameter that need to be considered in the design are diameter shrinkage and taper rate. The diameter of a culm was fairly equal within the height of 1 to 5 m and decreased from 5 m onwards. Upon drying, the culm of the larger diameter tended to shrink more than the smaller one. Thickness irregularity around the circumference of the internode wall was minor. The shrinkage of the internode wall was within 20%. The selection of culms for construction is best between the height of 1 and 5 m whereby the internodal length is more consistent.